“Build-a-ride”: an online simulation game for learning construction - Ismail, Balkhiz; Abdul Hadi, Nurulhudaya; Abd Wahab, Siti Rashidah Hanum (Universiti Teknologi MARA, Kedah, 2023)
The emergence of Generation Z in tertiary education has created a need for innovative adaptive learning approaches that cater to their distinct characteristics, including their avid use of the internet and social media, as well as their relatively shorter attention spans. Game-based learning has been identified as a promising method to enhance student engagement and motivation in this tech-savvy generation. “Build- A-Ride”, an Online Simulation Game, has been developed as a response to these needs. It aims to assist students in effectively memorizing complex technical terminologies by providing repeated exposure to the words within the game. Through gameplay, students reinforce their understanding and retention of subject-related information. The game also allows the lecturer to assess students' comprehension of the topic. In conclusion, “Build-A-Ride” offers an engaging, effective, and enjoyable way for Generation Z students to master technical terminology and improve their learning experience in construction-related topics. By harnessing the power of game-based learning and catering to the characteristics of this cohort, educators can bridge the gap between traditional teaching methods and the expectations of a technologydriven generation.